2000
DOI: 10.1159/000017430
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Differentiation in Human CNS Stem Cell Progeny by Leukemia Inhibitory Factor

Abstract: The generation of diverse types of neural cells during development occurs through the progressive restriction of the fate potential of neuroepithelial progenitor cells. This process is controlled by factors intrinsic and extrinsic to the cell. While the effect of extrinsic cues on multipotent stem cells of the murine central nervous system (CNS) is becoming clearer, little is known of neural stem cells of human origin. We sought to establish the roles played by two cytokines, leukemia inhibitory (LIF) and cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 42 publications
6
45
0
Order By: Relevance
“…Early passage (passages 10 -15) clonally derived glioblastoma multiforme cells underwent terminal differentiation upon removal of mitogens (34,36) and the subsequent addition of leukemia inhibitory factor to the medium, as shown previously for human fetal neural stem cells (24). Similar to normal neural stem cells (34), all of the glioblastoma multiforme clonal lines differentiated into GFAP-positive astrocytelike cells ( Fig.…”
Section: Selection and Expansion Of Neural Precursors From Adult Humasupporting
confidence: 69%
See 1 more Smart Citation
“…Early passage (passages 10 -15) clonally derived glioblastoma multiforme cells underwent terminal differentiation upon removal of mitogens (34,36) and the subsequent addition of leukemia inhibitory factor to the medium, as shown previously for human fetal neural stem cells (24). Similar to normal neural stem cells (34), all of the glioblastoma multiforme clonal lines differentiated into GFAP-positive astrocytelike cells ( Fig.…”
Section: Selection and Expansion Of Neural Precursors From Adult Humasupporting
confidence: 69%
“…To assess for multipotency, cells were plated at a density of 2.5 ϫ 10 4 cells/cm 2 onto Matrigel-coated glass coverslips (12 mm diameter) in the presence of leukemia inhibitory factor (10 ng/mL; ref. 24) for 7 to 10 days. Multiple immunofluorescence assays for neural antigens were performed as described by Gritti et al (21) and Galli et al (23).…”
Section: Methodsmentioning
confidence: 99%
“…Neural stem cells have been found in cultures of embryonic and adult murine brain, as well as embryonic human brain diencephalon, after epigenetic stimulation [13][14][15][16].…”
Section: Isolation and Expansion Of Human Adult Olfactory Bulb Stem Cmentioning
confidence: 99%
“…Neural stem cells with these characteristics have been found in cultures of embryonic and adult murine brain [10][11][12][13][14], as well as in human embryonic brain explants after epigenetic stimulation [15,16]. The SVZ is an intensive proliferative zone and the progeny of neural stem cells can either die or give rise to "neural progenitors" that migrate to the olfactory bulb [17].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] In order to evaluate the effect of acute stimulation with inflammatory cytokines on NPCs, we exposed neurospheres at early passages to TNF-a, IL-1b and IFN-g and analyzed the expression of 94 apoptosis-related mRNA by a custom RT-PCR array (Microfluidic Card, Applied Biosystems). Interestingly, we observed that in the presence of proinflammatory cytokines nestin-positive primitive neural cells express considerable amounts of TNF-a, TL1A and TRAIL mRNA, while showing no detectable CD95L (data not shown).…”
mentioning
confidence: 99%